2020
DOI: 10.1002/adhm.202001117
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralization: An Opportunity and Challenge of Nanoparticle Drug Delivery Systems for Cancer Therapy

Abstract: Biomineralization is a common process in organisms to produce hard biomaterials by combining inorganic ions with biomacromolecules. Multifunctional nanoplatforms are developed based on the mechanism of biomineralization in many biomedical applications. In the past few years, biomineralization-based nanoparticle drug delivery systems for the cancer treatment have gained a lot of research attention due to the advantages including simple preparation, good biocompatibility, degradability, easy modification, versat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 355 publications
(200 reference statements)
0
53
0
Order By: Relevance
“…20,21 Especially, biodegradability of nanomaterial carriers is a critical challenge in future clinical applications. 22 The coordination polymer consisting of Fe(III) and gallic acid (GA) has been widely used in drug delivery, 23 in which Fe(III) is coordinated with the -COOH of GA in unsaturated modality. 24,25 It can gradually degrade in response to the weakly acidic tumor microenvironment (TME), 26 and be effectively excreted from the body without causing long-term retention and toxicity problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Especially, biodegradability of nanomaterial carriers is a critical challenge in future clinical applications. 22 The coordination polymer consisting of Fe(III) and gallic acid (GA) has been widely used in drug delivery, 23 in which Fe(III) is coordinated with the -COOH of GA in unsaturated modality. 24,25 It can gradually degrade in response to the weakly acidic tumor microenvironment (TME), 26 and be effectively excreted from the body without causing long-term retention and toxicity problems.…”
Section: Introductionmentioning
confidence: 99%
“… 20,21 Especially, biodegradability of nanomaterial carriers is a critical challenge in future clinical applications. 22 …”
Section: Introductionmentioning
confidence: 99%
“…Biomineralization features the enrichment of inorganic ions on organic substrates to form hard tissue materials, , which plays an important role in the formation of hard tissue in living bodies, such as the physiological formation of bone and teeth . Calcification is one of the common biomineralization types in mammalian cells, which usually is initially mediated at the mitochondrial level, as mitochondrial calcification is considered an important physiological process that protects cells from calcium-induced cytotoxicity .…”
Section: Introductionmentioning
confidence: 99%
“…63 Nanoparticle delivery systems can potentially improve the efficacy and reduce the toxicity of DOX. 64 , 65 , 66 , 69 The Yan group reported that DOX combined with nanoparticles reduced the toxicity in the treatment of liver cancer. 67 …”
Section: Applications Of Carboranes As Boron Neutron Capture Therapy Agentsmentioning
confidence: 99%